Principal component analysis (PCA) in medical image processing using digital imaging and communications in medicine (dicom) medical images - DR. RM.VIDHYAVATHI (International Journal of Pharma and Bio Sciences, 2017)
The significant advancements in biological sciences have made remarkable developments in many fields including medical image management. This type of medical images is the essential part of doctors and radiologist to diagnose patient case. Digital Imaging and Communications in Medicine (DICOM) has been a universal standard for secured communication of medical contents over networks. Principal Component Analysis (PCA) is a powerful technique to identify the patterns of large data sets, offers a trendy statistical methodology to analyze multivariate data by constructing a succinct data representation using the dominant Eigen vectors of the data covariance matrix. This paper fully contributes the applications of PCA in the field of DICOM-based medical image processing. The results and discussions in this paper exhibited to prove its efficiency.